2014
DOI: 10.1177/1476718x14523748
|View full text |Cite
|
Sign up to set email alerts
|

Everyday routines: A window into the cultural organization of family child care

Abstract: Eco(logical)-cultural Theory suggests that a daily routine results from individuals adapting cultural ideas to the constraints of a local context or ecology. Using Ecocultural Theory, this research examined family child care providers' descriptions of daily activities and overall approach to understand cultural models. The results highlighted a predominant cultural model reflecting ideas of "natural" child development facilitated by a structured daily routine. However, an alternative model emphasizing flexibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…This finding highlights the transactional nature of development and how it is influenced by the cultural contexts in which participation takes place. In a similar fashion, Tonyan (2015) showed that family child care providers’ descriptions of “culturally organized ideals of care, or cultural models, held by adults can impact the kind of activities that children experience in their daily lives” (p. 312).…”
Section: Empirical Studies That Support the Cultural Microsystems Parmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding highlights the transactional nature of development and how it is influenced by the cultural contexts in which participation takes place. In a similar fashion, Tonyan (2015) showed that family child care providers’ descriptions of “culturally organized ideals of care, or cultural models, held by adults can impact the kind of activities that children experience in their daily lives” (p. 312).…”
Section: Empirical Studies That Support the Cultural Microsystems Parmentioning
confidence: 97%
“…This finding highlights the transactional nature of development and how it is influenced by the cultural contexts in which participation takes place. In a similar fashion, Tonyan (2015) showed that family child care providers' descriptions of "culturally organized ideals of care, or cultural models, held by adults can impact the kind of activities that children experience in their daily lives" (p. 312). Tonyan et al (2013) used an ecocultural model to develop a group-based approach to understand the relationship between beliefs and practice on child care providers from an archival analysis using the Observational Ratings of the Caregiving Environment.…”
Section: Culture As Part Of Schools and Other Learning Environmentsmentioning
confidence: 98%
“…However, in many of these contexts, play is not culturally indicated for learning per se; with learning viewed in terms of skill acquisition, mastery of content, highly-valued contributions to community, participation in oral language activities (e.g. story-telling, multi-participant conversational turn-taking, songs and rhyming), observation and modelling (Escayg and Kinkead-Clark, 2018 [93]; Tiko, 2017 [94]; Ukala and Agabi, 2017 [95]). The impact of travelling notions of play-for-learning manifests in research describing valiant efforts on behalf of educators attempting to mediate imported ideas about play within the existing culturally-derived ideological positions on curriculum and pedagogy held within their own countries (Gupta, 2020[96]).…”
Section: Play and Play-based Learningmentioning
confidence: 99%
“…Where such privileging occurs, cultural variations associated with both human-to-human and non-human-to-human interactions, alongside oral language and observational learning may not be embedded in approaches to teaching and learning [e.g. Escayg and Kinkead-Clark (2018 [93]); Tiko (2017 [94])].…”
Section: Research Papers By Typementioning
confidence: 99%
See 1 more Smart Citation